2000
DOI: 10.1021/es001223s
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Energy from the Marine Sediment−Water Interface

Abstract: Pairs of platinum mesh or graphite fiber-based electrodes, one embedded in marine sediment (anode), the other in proximal seawater (cathode), have been used to harvest low-level power from natural, microbe established, voltage gradients at marine sediment-seawater interfaces in laboratory aquaria. The sustained power harvested thus far has been on the order of 0.01 W/m2 of electrode geometric area but is dependent on electrode design, sediment composition, and temperature. It is proposed that the sediment/anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
302
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(313 citation statements)
references
References 14 publications
4
302
0
7
Order By: Relevance
“…Electrons are generated from the metabolism of the naturally occurring microorganism in the marine sediments. As such, benthic MFCs do not require the addition of any exogenous microorganisms or electron shuttles [1, 8,9]. Two separate benthic MFCs have been used to varying effect, the first, a prototype had a mass of 230 kg and a volume of 1.3 m −2 , and could sustain 24 mW or the equivalent of 16 alkaline D-cell batteries per year [7].…”
Section: Current Applications For Microbial Fuel Cellsmentioning
confidence: 99%
“…Electrons are generated from the metabolism of the naturally occurring microorganism in the marine sediments. As such, benthic MFCs do not require the addition of any exogenous microorganisms or electron shuttles [1, 8,9]. Two separate benthic MFCs have been used to varying effect, the first, a prototype had a mass of 230 kg and a volume of 1.3 m −2 , and could sustain 24 mW or the equivalent of 16 alkaline D-cell batteries per year [7].…”
Section: Current Applications For Microbial Fuel Cellsmentioning
confidence: 99%
“…The typical substrate for the anodic process is acetate although it has been shown that H 2 can also be used (Logan et al 2006). Waterlogged soils and sediments containing organic matter have been exploited for direct electrical current generation in sediment-MFCs (Donovan et al 2011;Reimers et al 2001;Tender et al 2008). A drawback of sediment-MFCs is the low flux of organic matter towards the anode, limiting high current production.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of BESs when using two compartments is that they not solely convert compounds but also separate oxidation and reduction products, which makes it possible to extract useful products out of wastes. Nowadays, BES with bioanodes uses electron donors derived from wastes (e.g., wastewaters; Logan 2005), sediments (Reimers et al 2001), processed energy crops (as cellulose; Niessen et al 2005;Ren et al 2007;Rezaei et al 2009), photosynthetic microorganisms (Strik et al 2008b;Chiao et al 2006;Fu et al 2009), or in situ photosynthesized plant rhizodeposits (Strik et al 2008a;De Schamphelaire et al 2008). BESs, like MFCs treating wastewater, combine energy harvesting with necessary wastewater cleaning.…”
Section: Introductionmentioning
confidence: 99%